INTERNET-BASED LEARNING MEDIA IN THE DIGITAL ERA OF EFL LEARNING IN ENGLISH EDUCATION MASTER PROGRAM (S2 BE)” - Yohanes Gatot Sutapa Yuliana (Journal of English Educational Study (JEES), 2022)
In line with the rapid development of technology and the changing times that are increasingly digitalistic, without boundaries, the use of the Internet for education has experienced a very significant development of a sine qua non condition. Internet technology, which has a large enough influence in the world of education, demands a reciprocal awareness of professionalism from all parties around its influence. This media is part of the learning process that tends to be borderless and can be an alternative that must be adapted and optimized in the digitalistic cyber era, as a relevant learning medium. This research is to optimize the tendency of the Internet as a medium of learning activities that are acceptable, fun, relevant and adaptable to the progress and demands of the times that are surrounded by S2BE FKIP UNTAN students. With the ADD design from ADDIE that is tailored to the needs and limitations of activities, this study takes the subject of S2 BE students with EFL being the major with an output target oriented to the creation of the development of EFL learning management that uses Internet technology as a medium. It is hoped that this research can be a reference for the development of EFL learning in a more integrated and maximal way so that the learning outcomes targeted can contribute to the development of human resources for prospective lecturers in West Kalimantan in a more comprehensive and effective manner. Keywords: Internet, Learning, EFL, Development, Digital era